11.0k views
5 votes
Which of the following occurs within the solution process for ∛(5x-2)-∛4x=0

A.)squaring both sides once
B.)squaring both sides twice
C.)cubing both sides once
D.)cubing both sides twice

2 Answers

5 votes

Answer:

C

Explanation:

rearrangeing:-

∛(5x - 2) = ∛((4x)

Cubing both sides:-

5x - 2 = 4x

User Nuri YILMAZ
by
6.0k points
6 votes

Answer:

cubing both sides once

Explanation:

∛(5x-2)-∛4x=0

To solve this equation , we move second term to the other side

Add cube root (4x) on both sides


\sqrt[3]{5x-2} =\sqrt[3]{4x}

Now we remove cube root.

To remove cube root we take cube on both sides because cube and cube root will get cancelled.


(\sqrt[3]{5x-2})^3=(\sqrt[3]{4x})^3


5x-2=4x

So, cubing both sides once

User Hassan Jalil
by
6.2k points